1978
DOI: 10.1111/j.1600-0528.1978.tb01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral and dental affections in mercury‐exposed workers

Abstract: A total of 222 mercury-exposed workers in the Chlor-Alkali plant in Kuwait were investigated for oral and dental affections. The levels of mercury-vapor ranged from 566.6 microgram/m3 to 0.3 microgram/m3 in different parts of the factory. The periods of exposure varied from 1 to 11 years. Although the level of mercury vapor in the air and the period of exposure proved to be the main factors as regards the oral signs and symptoms, the oral hygiene condition and the individual sensitivity played substantial role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…[13] The most common oral mucosal lesion in the study was leukoplakia. Mandibular sulcus region was the most common site of ulceration in this study and in another study conducted by Fahmy[14] on workers engaged in some other occupation. This may be due to the habit of keeping the tobacco quid most of the times in the mandibular sulcus region.…”
Section: Discussionsupporting
confidence: 71%
“…[13] The most common oral mucosal lesion in the study was leukoplakia. Mandibular sulcus region was the most common site of ulceration in this study and in another study conducted by Fahmy[14] on workers engaged in some other occupation. This may be due to the habit of keeping the tobacco quid most of the times in the mandibular sulcus region.…”
Section: Discussionsupporting
confidence: 71%
“…The results with the CPITN index were also compared with previously published data for another similar population. Results-There was no significant difference between the exposed workers and the referents with respect to the number of remaining [4][5][6][7] In subjects with ongoing mercury exposure,35 increased periodontal disease, soreness of the mouth, loose teeth, and in one instance increased number of missing teeth compared with controls,3 have been reported. A study on 642 workers exposed to mercury and 382 controls, however, reported no correlation of oral abnormalities with mercury exposure,6 and in a study performed on 82 people currently exposed to mercury and 82 controls with similar oral hygiene between the groups, no effect of mercury exposure was found on the occurrence of gingivitis, periodontitis, or the number of missing teeth.7…”
mentioning
confidence: 99%